2016
DOI: 10.1016/j.jadohealth.2016.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents' Responses to Pictorial Warnings on Their Parents' Cigarette Packs

Abstract: Purpose Pictorial cigarette pack warnings are a promising policy solution to increase smoking cessation among adults. However, little is known regarding adolescents' responses to pictorial warnings, particularly in real-world settings. Methods Participants were 112 adolescent children, ages 13–17, whose parents received either text-only warnings on the side of their cigarette packs or pictorial warnings on the top half of the front and back of their cigarette packs for 4 weeks as part of a trial. We measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(43 citation statements)
references
References 33 publications
1
42
0
Order By: Relevance
“…We found that pictorial warnings cued conversations among adolescents [ 15 ], building on previous research that pictorial warnings spark conversations among adults [ 5 , 26 28 ] (Morgan JC, Golden SD, Noar SM, Ribisl KM, Southwell BG, Jeong M, Hall MG, Brewer NT: Conversations about pictorial cigarette pack warnings: Theoretical mechanisms of influence impact quit attempts, submitted). Pictorial warnings offered an important opportunity for adolescents to broach the topic of smoking cessation with their parents (and sometimes with their friends).…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…We found that pictorial warnings cued conversations among adolescents [ 15 ], building on previous research that pictorial warnings spark conversations among adults [ 5 , 26 28 ] (Morgan JC, Golden SD, Noar SM, Ribisl KM, Southwell BG, Jeong M, Hall MG, Brewer NT: Conversations about pictorial cigarette pack warnings: Theoretical mechanisms of influence impact quit attempts, submitted). Pictorial warnings offered an important opportunity for adolescents to broach the topic of smoking cessation with their parents (and sometimes with their friends).…”
Section: Discussionsupporting
confidence: 54%
“…Another found that strong negative emotions mediate the relationship between perceived graphicness of cigarette warning labels and increased negative beliefs about smoking [ 14 ]. One limitation of past research on adolescents’ responses to pictorial warnings is that studies have been conducted almost exclusively in laboratory settings [ 15 ]. Also, there is a lack of research that specifically investigates how the vulnerable population of children of smokers react to pictorial warning labels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Health warnings on tobacco packaging are among the most cost-effective policy interventions to communicate health information, given their reach and frequency of exposure [ 13 , 14 ]. Although text-only warnings can be effective at informing smokers of health effects [ 13 ], pictorial warnings are acknowledged as superior to text-only warnings on most metrics [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], particularly if they are prominent and feature graphic, emotion-arousing images [ 13 , 20 ]. A recent meta-analysis of experimental studies concluded that, compared to text-only warnings, pictorial warnings were more effective for attracting and holding attention, eliciting stronger cognitive and emotional reactions, eliciting more negative attitudes toward packs/brands and to smoking, and increasing intentions to quit or not start smoking [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we recruited 112 adolescent children of adults (age range: 13–17 years) who participated in the RCT for an ancillary study of responses to pictorial warnings on the parents’ cigarette packs. A full description of the study design, recruitment, and procedures appears elsewhere [ 35 ]. We conducted phone interviews with the adolescents and provided a $40 incentive.…”
Section: Methodsmentioning
confidence: 99%